Contralateral vs. Ipsilateral Approach to Superior Hypophyseal Artery Aneurysms: An Anatomical Study and Morphometric Analysis - Sahin, Balkan; Aydin, Serdar Onur; Yilmaz, Mehmet Ozgur; Saygi, Tahsin; Hanalioglu, Sahin; Akyoldas, Goktug; Baran, Oguz; Kiris, Talat (Frontiers in Surgery, 2022)
Introduction: Surgical clipping of superior hypophyseal artery (SHA) aneurysms is a challenging task for neurosurgeons due to their close anatomical relationships. The development of endovascular techniques and the difficulty of surgery have led to a decrease in the number of surgical procedures and thus the experience of neurosurgeons in this region. In this study, we aimed to reveal the microsurgical anatomy of the ipsilateral and contralateral approaches to SHA aneurysms, and define their limitations via morphometric analyses of radiological anatomy, 3D modeling and surgical illustrations. Method: Five fixed and injected cadaver heads underwent dissections. In order to make morphometric measurements, 75 cranial MRI scans were reviewed. Cranial scans were rendered with a module and used to produce 3D models of different anatomical structures. In addition a medical illustration was drawn which shows different sizes of aneurysms and surgical clipping approaches. Results: For the contralateral approach, pterional craniotomy and sylvian dissection was performed. The contralateral SHA was reached from the prechiasmatic area. The dissected SHA was approached with an aneurysm clip and maneuverability was evaluated. For the ipsilateral approach, pterional craniotomy and sylvian dissection was performed. The ipsilateral SHA was reached by mobilizing the left optic nerve with left optic nerve unroofing and left anterior clinoidectomy. MRI measurements showed that; area of the prechiasm was 90.4±36.6mm2 (prefixed:46.9 ±10.4 mm2, normofixed: 84.8±15.7 mm2, postfixed:137.2±19.5 mm2 , p<0.001), distance between the anterior aspect of the optic chiasm and the limbus sphenoidale was 10.0± 3.5mm (prefixed: 5.7±0.8 mm, normofixed: 9.6±1.6 mm, postfixed:14,4± 1,6mm, p < 0.001), optic nerves’ interneural angle was 65.2°±10.0° (prefixed: 77.1°±7.3, normofixed: 63.6°± 7.7° , postfixed: 57.7 °±5.7°, p: 0.010). Conclusions: Anatomic dissections along with 3D virtual model simulation and illustrations demonstrated that contralateral approach would potentially allow for proximal control and neck control/clipping in smaller SHA aneurysm with relatively minimal retraction of contralateral optic nerve in the setting of pre- or normofixed chiasm, and ipsilateral approach requires anterior clinodectomy and optic unroofing with considerable optic nerve mobilization to effectively control proximal ICA and clip the aneurysm neck.